2014
DOI: 10.1136/bmjspcare-2013-000514
|View full text |Cite
|
Sign up to set email alerts
|

Preference for a single or shared room in a UK inpatient hospice: patient, family and staff perspectives

Abstract: Objective: This study investigated the preferences of patients, family and staff for single or shared rooms in a UK hospice.Method: Semi-structured interviews were conducted with patients, informal carers and staff at a hospice, focussing on room type preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…These findings are consistent with the study of Williams y Gardiner [ 50 ], which states that PCU should have collective and single rooms since the choice between these two types of room is not unanimous among patients.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the study of Williams y Gardiner [ 50 ], which states that PCU should have collective and single rooms since the choice between these two types of room is not unanimous among patients.…”
Section: Discussionsupporting
confidence: 92%
“…This supports our finding of patients preferring single bedrooms when feeling very sick. Studies of patients in a hospice and patients with advanced cancer also show that patients seek the company of fellow patients in multi bedrooms but when death is near single rooms are preferable according to both patients and staff [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…In a single bedroom, patient integrity and privacy seems easier to withhold, but the surveillance of patients is often easier in a multi bedroom as the staff can monitor more patients at a time [11][12][13]. Patients enjoy the security of being visible to staff and to each other [10].…”
Section: Introductionmentioning
confidence: 99%
“…The act of viewing nature through a window may help alleviate isolation and loneliness, which may have a positive impact on patients [52]. Similarly, studies have demonstrated that listening to soothing nature sounds such as birdsong can reduce patient anxiety and agitation [53,54].…”
Section: Gardens As a Multisensory Intervention For Healing In The Enmentioning
confidence: 99%
“…Therapeutic landscapes and healing gardens with a variety of features have the tendency to stimulate restoration and other positive influences on healthcare occupants [21,45]. Research evidence found that hospital garden users reported positive mood change and experience from time spent in observing nature [52]. Similarly, studies have shown that therapeutic gardens can assist dementia patients to reduce behavior problems caused by fear and anxiety during post-stroke rehabilitation procedures [49,65].…”
Section: Therapeutic Dimensions Of Nature Views and Access To Gardensmentioning
confidence: 99%